Theory‐Guided Synthesis of a Metastable Lead‐Free Piezoelectric Polymorph. Issue 25 (10th May 2018) - Garten, Lauren M.; Dwaraknath, Shyam; Walker, Julian; Mangum, John S.; Ndione, Paul F.; Park, Yoonsang; Beaton, Daniel A.; Gopalan, Venkatraman; Gorman, Brian P.; Schelhas, Laura T.; Toney, Michael F.; Trolier‐McKinstry, Susan; et al.
Abstract: Many technologically critical materials are metastable under ambient conditions, yet the understanding of how to rationally design and guide the synthesis of these materials is limited. This work presents an integrated approach that targets a metastable lead‐free piezoelectric polymorph of SrHfO3 . First‐principles calculations predict that the previous experimentally unrealized, metastable P4 mm phase of SrHfO3 should exhibit a direct piezoelectric response (d33 ) of 36.9 pC N −1 (compared to d 33 = 0 for the ground state). Combining computationally optimized substrate selection and synthesis conditions lead to the epitaxial stabilization of the polar P4 mm phase of SrHfO3 on SrTiO3 . The films are structurally consistent with the theory predictions. A ferroelectric‐induced large signal effective converse piezoelectric response of 5.2 pm V −1 for a 35 nm film is observed, indicating the ability to predict and target multifunctionality. This illustrates a coupled theory‐experimental approach to the discovery and realization of new multifunctional polymorphs. Abstract : An integrated theory–experimental approach to the stabilization of a predicted metastable lead‐free piezoelectric polymorph of SrHfO3 is described. Computationally identified substrates and synthesis conditions lead to the epitaxial stabilization of the polar P4 mm phase of SrHfO3 . A ferroelectric‐induced piezoelectric response of 5.2 pm V −1 for a 35 nm film is observed, indicating the ability to achieve the predicted multifunctionality.